MODELING OF THE CHARACTER’S PRIVATE WORLD IN THE URIZH TEXT BY HALYNA PAHUTIAK - Сіренко, С. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The patterns of modeling of the character’s private world in the Urizh text by Halyna Pahutiak («The Mustard seed», «The Gentleman in a Black Suit with Shiny buttons», «The Gothic of Urizh», «Sunset in Urizh») through the prism of Fictional Worlds Theory are analyzed, including its structure (Knowledge World, Obligation World, Wish World, Intend World, Fantasy World, Assumption World, Prediction World), the character’s perception of reality and motivational model are investigated.